Water on Mars—A Literature Review - Mohammad Nazari-Sharabian; Mohammad Aghababaei; Moses Karakouzian; Mehrdad Karami (Galaxies, 2020)
To assess Mars’ potential for both harboring life and providing useable resources for future human exploration, it is of paramount importance to comprehend the water situation on the planet. Therefore, studies have been conducted to determine any evidence of past or present water existence on Mars. While the presence of abundant water on Mars very early in its history is widely accepted, on its modern form, only a fraction of this water can be found, as either ice or locked into the structure of Mars’ plentiful water-rich materials. Water on the planet is evaluated through various evidence such as rocks and minerals, Martian achondrites, low volume transient briny outflows (e.g., dune flows, reactivated gullies, slope streaks, etc.), diurnal shallow soil moisture (e.g., measurements by Curiosity and Phoenix Lander), geomorphic representation (possibly from lakes and river valleys), and groundwater, along with further evidence obtained by probe and rover discoveries. One of the most significant lines of evidence is for an ancient streambed in Gale Crater, implying ancient amounts of “vigorous” water on Mars. Long ago, hospitable conditions for microbial life existed on the surface of Mars, as it was likely periodically wet. However, its current dry surface makes it almost impossible as an appropriate environment for living organisms; therefore, scientists have recognized the planet’s subsurface environments as the best potential locations for exploring life on Mars. As a result, modern research has aimed towards discovering underground water, leading to the discovery of a large amount of underground ice in 2016 by NASA, and a subglacial lake in 2018 by Italian scientists. Nevertheless, the presence of life in Mars’ history is still an open question. In this unifying context, the current review summarizes results from a wide variety of studies and reports related to the history of water on Mars, as well as any related discussions on the possibility of living organism existence on the planet.